Single Umbilical Artery and Associated Systemic Anomalies in Foetal and Perinatal Autopsy: An Observational Study - Chandrahas Kotian; Milana Basavraja Halehuru; Hephzibah Rani; Aneel Myageri; Ravikala Vittal Rao (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: Single Umbilical Artery (SUA) is a congenital anomaly that can occur either as an isolated finding or in association with other systemic anomalies. Several studies have reported that SUA is linked to dysplastic kidneys, ventricular septal defects, oesophageal atresia, spina bifida, diaphragmatic hernia and cystic hygromas. Therefore, investigating cases of SUA in autopsies is crucial. Aim: To estimate the frequency of SUA in foetal autopsies and determine the association between SUA and other systemic anomalies. Materials and Methods: The present ambispective observational study was conducted in the Department of Pathology, Shri Dharmasthala Manjunatheshwara College of Medical Sciences and Hospital, Dharwad, Karnataka, India, over a 13 year period from January 2009 to December 2021. A total of 63 cases of SUA detected during foetal autopsies were included. Factors such as age, parity and multiple births were collected where available. The hospital-based frequency of SUA was calculated as a percentage. The association between SUA and systemic anomalies was assessed using the Chi-square test. Results: A total of 1338 perinatal autopsies were performed during the study period, with SUA present in 63 (4.70%) cases. The most common associated anomaly was genitourinary defects identified in 16 (25.39%) cases. However, a statistically significant association was observed with musculoskeletal (11.11%), nervous (11.11%), and gastrointestinal system anomalies (19.04%) with a p-value of <0.0001. Conclusion: In the present study, SUA accounted for 4.70% of the foetal autopsies conducted during the study period. The most common associated anomalies were bilateral cystic kidneys, and VATER (Vertebral, Anal, Tracheo-oesophageal, and Renal anomalies) was the most common syndromic associations with SUA.